Association between weight bias internalization and metabolic syndrome among treatment‐seeking individuals with obesity. Issue 2 (26th January 2017) - Pearl, Rebecca L.; Wadden, Thomas A.; Hopkins, Christina M.; Shaw, Jena A.; Hayes, Matthew R.; Bakizada, Zayna M.; Alfaris, Nasreen; Chao, Ariana M.; Pinkasavage, Emilie; Berkowitz, Robert I.; Alamuddin, Naji
Abstract : Objective: Weight stigma is a chronic stressor that may increase cardiometabolic risk. Some individuals with obesity self‐stigmatize (i.e., weight bias internalization, WBI). No study to date has examined whether WBI is associated with metabolic syndrome. Methods: Blood pressure, waist circumference, and fasting glucose, triglycerides, and high‐density lipoprotein cholesterol were measured at baseline in 178 adults with obesity enrolled in a weight‐loss trial. Medication use for hypertension, dyslipidemia, and prediabetes was included in criteria for metabolic syndrome. One hundred fifty‐nine participants (88.1% female, 67.3% black, mean BMI = 41.1 kg/m 2 ) completed the Weight Bias Internalization Scale and Patient Health Questionnaire (PHQ‐9, to assess depressive symptoms). Odds ratios and partial correlations were calculated adjusting for demographics, BMI, and PHQ‐9 scores. Results: Fifty‐one participants (32.1%) met criteria for metabolic syndrome. Odds of meeting criteria for metabolic syndrome were greater among participants with higher WBI, but not when controlling for all covariates (OR = 1.46, 95% CI = 1.00–2.13, P  = 0.052). Higher WBI predicted greater odds of having high triglycerides (OR = 1.88, 95% CI = 1.14–3.09, P  = 0.043). Analyzed categorically, high (vs. low) WBI predicted greater odds of metabolic syndrome and high triglycerides ( P s < 0.05). Conclusions: Individuals with obesity who self‐stigmatize may have heightened cardiometabolic risk. Biological and behavioral pathways linking WBI and metabolic syndrome require further exploration.